Risk Management Analysis of Hospital Management Information System (SIMRS) at ABC Hospital using ISO 31000 - Muhammad Aminudidin Yafie; Budhi Setianto; Agus Aan Addriansyah; Susanto, Fajar Annas (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2023)
A hospital is a health institution that serves as a center for providing care and treatment to individuals who are ill. To ensure optimal service delivery, the regulations of the Indonesian Ministry of Health mandate that every hospital in Indonesia must implement and manage the development of a Hospital Management Information System (SIMRS). ABC Hospital, a private institution, has been utilizing SIMRS since 2002. Risk management at ABC Hospital follows a structured approach encompassing five stages: communication and consultation, context determination, and risk assessment, which includes risk identification, analysis, evaluation, treatment, and monitoring. The results of this risk analysis enable ABC Hospital to prevent and minimize risks while addressing them according to their impact and priority. Based on research findings: (1) Governance management in the SIMRS unit at ABC Hospital aligns with the requirements of ISO 31000:2018; (2) Potential risks identified include the absence of certain features in the SIMRS program and inconsistent application of existing Standard Operating Procedures (SOPs); (3) The hospital's SIMRS faces 27 risks, categorized into 9 low risks, 3 moderate risks, and 15 high risks; (4) To mitigate these risks, it is recommended that procedures be strengthened and the existing application programs be enhanced.